Lipid emulsions attenuate the inhibition of carnitine acylcarnitine translocase induced by toxic doses of local anesthetics in rat cardiomyoblasts. (5th January 2022) - Ok, Seong-Ho; Kang, Dawon; Lee, Soo Hee; Kim, Hyun-Jin; Ahn, Seung Hyun; Sohn, Ju-Tae
The aim of this study was to examine the effects of lipid emulsions on carnitine palmitoyltransferase I (CPT-I), carnitine acylcarnitine translocase (CACT), carnitine palmitoyltransferase II (CPT-II), and the mitochondrial dysfunctions induced by toxic doses of local anesthetics in H9c2 rat cardiomyoblasts. The effects of local anesthetics and lipid emulsions on the activities of CPT-I, CACT, and CPT-II, and concentrations of local anesthetics were examined. The effects of lipid emulsions, N-acetyl-L-cysteine (NAC), and mitotempo on the bupivacaine-induced changes in cell viability, reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP), and intracellular calcium levels were examined. CACT, without significantly altering CPT-I and CPT-II, was inhibited by toxic concentration of local anesthetics. The levobupivacaine- and bupivacaine-induced inhibition of CACT was attenuated by all concentrations of lipid emulsion, whereas the ropivacaine-induced inhibition of CACT was attenuated by medium and high concentrations of lipid emulsion. The concentration of levobupivacaine was slightly attenuated by lipid emulsion. The bupivacaine-induced increase of ROS and calcium and the bupivacaine-induced decrease of MMP were attenuated by ROS scavengers NAC and mitotempo, and the lipid emulsion. Collectively, these results suggested that the lipid emulsion attenuated the levobupivacaine-induced inhibition of CACT, probably through the lipid emulsion-mediated sequestration of levobupivacaine.